Using Cognitive Mapping to Longitudinally Examine Political Brand Associations. Issue 3 (3rd July 2019) - MacDonald, Alexander Ewan; Sherlock, Roger; Hogan, John
Abstract : This paper uses cognitive mapping techniques to understand how brand associations, an important aspect of political brand equity are formed, differ, and change, from the perspective of citizens, across the four largest Irish political parties between 2013 and 2016. The paper focuses in particular upon the strength, favourability and uniqueness of these brand associations. The results constitute a first attempt to longitudinally explore changing political brand associations through cognitive mapping techniques, using data generated with the participation of hundreds of citizens. Our findings suggest that this approach can contribute to our understanding of how and why political brand associations change over time.